PENGARUH PROMOSI ONLINE DAN KERAGAMAN PRODUK DALAM MENENTUKAN KEPUASAN KONSUMEN PADA HEALTHYMASK.IDN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Diana, Meli Fita; Wiryaningtyas, Dwi Perwitasari; Harisandi, Yudhistira (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Online business has become the most popular business with a strong market in recent years. The increasing number of internet service users has resulted in online business experiencing rapid development. The purpose of this study was to analyze and examine the effect of online promotion and product diversity on consumer satisfaction at Healthymask.idn through purchasing decisions. This research is a quantitative research. The population in this study are Healthymsk.idn consumers. The sampling technique used is simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM).The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that online promotion has a significant effect on consumer satisfaction, online promotion has a significant effect on purchasing decisions, product diversity has a significant effect on purchasing decisions, product diversity is not proven to have a significant effect on consumer satisfaction, purchase decisions have an effect significant to consumer satisfaction. The results of the indirect effect hypothesis test show that the online promotion variable on consumer satisfaction through purchasing decisions has a significant positive effect, product diversity on consumer satisfaction through purchasing decisions has a significant positive effect.